Diseño de la iluminación de las canchas de voleibol del complejo deportivo universitario utilizando el SOFTWARE CALCULUX. - Moreno Betancourth, José Luis (2010)
The present investigation topic is a non alone contribution to improve the illumination of the exterior of the court of volleyball of the complex sport university student of the Algeria, but rather the same one can be executed in other sport facilities in the community lojana, in the same one it is developed through the electronic software that allows the schematic capture and logical programming. The investigation allowed to fulfill the general objective that is to design the system of illumination through the software quick lux for the external facilities of the courts of volleyball of the complex sport university student of the "Algeria" and the specific objectives as: To know the handling and application of the software quick lux in the design and simulation of illumination, to use the software quick lux in appropriate form for the installation of you would illuminate them external of the volleyball courts and to socialize the handling of the software quick lux that allows the appropriate use of this electronic tool. The methodology used for the development of the scientific work an orderly and complex process that took us to guide us from the general thing to the specific thing, was it allowed it to break down in parts the complex aspects. The present method in the investigation was carried out through several stages in a progressive and upward way, through the following steps: Observation, demonstration, decomposition of the phenomenon, enumeration of the parts, ordination, classification and final report, through the practical work of using the software calcu lux for the illumination of external of the sport court of volleyball. As general conclusion it was determined in the sport applications, the parameters of quality and number of projectors in the first evaluation, they turned out to be very similar. That which indicates that the theoretical and practical methods are feasible, without forgetting the characteristics of the area, of the atmosphere and of the teams they can be different according to the conditions and assumed values.